Simultaneous Temperature and Acoustic Sensing with Coherent Correlation OTDR - Sandmann, Andre; Azendorf, Florian; Eiselt, Michael (2023 Optical Fiber Communications Conference and Exhibition (OFC), 2023)
Superimposed temperature variations and dynamic strain applied through a 400 Hz acoustic signal on a 195 m single-mode fiber section are successfully measured using a coherent correlation optical time domain reflectometry as an interrogator.